A potential role of the renin-angiotensin-aldosterone system in epithelial-to-mesenchymal transition-induced renal abnormalities: Mechanisms and therapeutic implications. (August 2019) - Balakumar, Pitchai; Sambathkumar, Ramanathan; Mahadevan, Nanjaian; Muhsinah, Abdullatif Bin; Alsayari, Abdulrhman; Venkateswaramurthy, Nallasamy; Jagadeesh, Gowraganahalli
Graphical abstract: Abstract: Epithelial-to-mesenchymal transition (EMT) is an orchestrated event where epithelial cells progressively undergo biochemical changes and transition into mesenchymal-like cells by gradually losing their epithelial characteristics. EMT plays a crucial pathologic role in renal abnormalities, especially renal fibrosis. A number of bench studies suggest the potential involvement of renin-angiotensin-aldosterone system (RAAS) in renal EMT process and associated renal abnormalities. EMT appears to be an important pathologic mechanism for the deleterious renal effects of angiotensin II and aldosterone, the two major RAAS components. Mechanistically, the renal RAAS-TGF-β-Smad3 signalling pathway plays an important pathologic role in EMT-associated renal abnormalities. Intriguingly, the RAAS antagonists such as losartan, telmisartan, eplerenone, and spironolactone have the potential to prevent renal EMT in bench studies. This review describes the key mechanistic role of RAAS overactivation in EMT-induced renal abnormalities. Moreover, drugs interrupting the RAAS at different levels in the cascade ameliorating the EMT-associated renal abnormalities are described.